Dysbalance of ACE2 levels – a possible cause for severe COVID‐19 outcome in COPD. (12th May 2021) - Fließer, Elisabeth; Birnhuber, Anna; Marsh, Leigh M; Gschwandtner, Elisabeth; Klepetko, Walter; Olschewski, Horst; Kwapiszewska, Grazyna
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) poses a serious threat to healthcare systems worldwide. Binding of the virus to angiotensin‐converting enzyme 2 (ACE2) is an important step in the infection mechanism. However, it is unknown if ACE2 expression in patients with chronic lung diseases (CLDs), such as chronic obstructive pulmonary disease (COPD), idiopathic pulmonary arterial hypertension (IPAH), or pulmonary fibrosis (PF), is changed as compared to controls. We used lung samples from patients with COPD ( n = 28), IPAH ( n = 10), and PF ( n = 10) as well as healthy control donor ( n = 10) tissue samples to investigate the expression of ACE2 and related cofactors that might influence the course of SARS‐CoV‐2 infection. Expression levels of the ACE2 receptor, the putative receptor CD147/ BSG, and the viral entry cofactors TMPRSS2 (transmembrane serine protease 2), EZR, and FURIN were determined by quantitative PCR and in open‐access RNA sequencing datasets. Immunohistochemical and single‐cell RNA sequencing (scRNAseq) analyses were used for localization and coexpression, respectively. Soluble ACE2 (sACE2) plasma levels were analyzed by enzyme‐linked immunosorbent assay. In COPD as compared to donor, IPAH, and PF lung tissue, gene expression of ACE2, TMPRSS2, and EZR was significantly elevated, but circulating sACE2 levels were significantly reduced in COPD and PF plasma compared to healthy control and IPAH plasma samples. Lung tissue expressions of FURIN and CD147/ BSG were downregulated in COPD. None of these changes were associated with changes in pulmonary hemodynamics. Histological analysis revealed coexpression of ACE2, TMPRSS2, and Ezrin in bronchial regions and epithelial cells. This was confirmed by scRNAseq analysis. There were no significant expression changes of the analyzed molecules in the lung tissue of IPAH and idiopathic PF as compared to control. In conclusion, we reveal increased ACE2 and TMPRSS2 expression in lung tissue with a concomitant decrease of protective sACE2 in COPD patients. These changes represent the possible risk factors for an increased susceptibility of COPD patients to SARS‐CoV‐2 infection.